Legislation and applicable concepts to protected natural areas in Peru - Solano, Pedro (2013)
There are 78 protected areas in Peru covering 22 million hectares corresponding almost 17 percent of national territory. This article reviews essential aspects of protected natural areas studying scopes, purposes, types, categories and levels such as: requirements for setting, amendment and repeal; activities allowed and forbidden within them; institutional management, among others. Finally, this work concludes with some brief thoughts on legal and institutional challenges of the Sistema Nacional de Áreas NaturalesProtegidas por el Estado (SINANPE) (National System of State ProtectedNatural Areas).